2022
DOI: 10.1093/ajcn/nqab341
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of unconditional cash transfers combined with lipid-based nutrient supplement and/or behavior change communication to prevent stunting among children in Pakistan: a cluster randomized controlled trial

Abstract: Background In Pakistan, the prevalence of stunting among children under-five years has remained above WHO critical thresholds (≥30%) over the last two decades. Objective We hypothesized that an unconditional cash transfer (UCT) combined with lipid-based nutrient supplement (LNS) and/or social and behavior change communication (SBCC) will prevent stunting among children 6-23 months of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Most RCTs use more "pragmatic designs" that attempt to recruit from routine clinical practices or other relevant convenience sample settings; indeed, a search of the ClinicalTrials.gov database at the (US) National Library of Medicine (https://clinicaltrials.gov/) using the key words "representative sample" and "probability sample" finds only 8 registered clinical trials out of over 450,000 that could be confirmed to have recruited subjects in something reasonably approximating a probability sample from a well defined population, of which 7 have reported results. [11][12][13][14][15][16][17] As noted by Olson, 18 bias in the estimation of population causal effects from RCT arises from heterogeneity in treatment effects and systematic selection bias in the RCT with respect to the effect modifiers. Hence the basic approach revolves around accounting for differences between RCT and population effect modifiers.…”
Section: Brief Review Of Transportability Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most RCTs use more "pragmatic designs" that attempt to recruit from routine clinical practices or other relevant convenience sample settings; indeed, a search of the ClinicalTrials.gov database at the (US) National Library of Medicine (https://clinicaltrials.gov/) using the key words "representative sample" and "probability sample" finds only 8 registered clinical trials out of over 450,000 that could be confirmed to have recruited subjects in something reasonably approximating a probability sample from a well defined population, of which 7 have reported results. [11][12][13][14][15][16][17] As noted by Olson, 18 bias in the estimation of population causal effects from RCT arises from heterogeneity in treatment effects and systematic selection bias in the RCT with respect to the effect modifiers. Hence the basic approach revolves around accounting for differences between RCT and population effect modifiers.…”
Section: Brief Review Of Transportability Methodsmentioning
confidence: 99%
“…Most RCTs use more “pragmatic designs” that attempt to recruit from routine clinical practices or other relevant convenience sample settings; indeed, a search of the ClinicalTrials.gov database at the (US) National Library of Medicine (https://clinicaltrials.gov/) using the key words “representative sample” and “probability sample” finds only 8 registered clinical trials out of over 450,000 that could be confirmed to have recruited subjects in something reasonably approximating a probability sample from a well defined population, of which 7 have reported results. 1117…”
Section: Previous Workmentioning
confidence: 99%
“…Menurut Little et al 86 , bantuan tunai yang dikombinasikan dengan pemberian makanan lebih efektif menurunkan stunting dibandingkan dengan bantuan tunai saja. Di Pakistan, Soofi et al 87 Separuh balita stunting (54,1%) mendapatkan bantuan Aseskin (Tabel 2). Proporsi ini lebih rendah dibandingkan dengan proporsi di Kota Palangkaraya, 91,9% 89 , dan Ghana, 70,1% 90 .…”
Section: Hasil Dan Pembahasanunclassified
“…Among the reasons behind this greater acceptance is the perception that CBI increases beneficiary agency, as they can often decide how to use the cash for their specific needs of goods or services; it is a cost-effective intervention, has positive impacts on local economies, and improves beneficiary satisfaction. However, CBIs do not appear to consistently reduce the risk of malnutrition in children, and there is no evidence on its ability to reduce excess mortality [6][7][8][9][10]. Even in nonhumanitarian contexts debate continues on the relative merits of conditional and unconditional transfers on child health and nutrition and how that may play out in different contexts [11,12].…”
Section: Introductionmentioning
confidence: 99%